4h+2h+3h-9h+3h-2=19

Simple and best practice solution for 4h+2h+3h-9h+3h-2=19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4h+2h+3h-9h+3h-2=19 equation:


Simplifying
4h + 2h + 3h + -9h + 3h + -2 = 19

Reorder the terms:
-2 + 4h + 2h + 3h + -9h + 3h = 19

Combine like terms: 4h + 2h = 6h
-2 + 6h + 3h + -9h + 3h = 19

Combine like terms: 6h + 3h = 9h
-2 + 9h + -9h + 3h = 19

Combine like terms: 9h + -9h = 0
-2 + 0 + 3h = 19
-2 + 3h = 19

Solving
-2 + 3h = 19

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 3h = 19 + 2

Combine like terms: -2 + 2 = 0
0 + 3h = 19 + 2
3h = 19 + 2

Combine like terms: 19 + 2 = 21
3h = 21

Divide each side by '3'.
h = 7

Simplifying
h = 7

See similar equations:

| 700+.5=737 | | 2x-x+8=7 | | y=ax^2-b | | 3c^2-8c+4=0 | | x^2-8y+6x+25+y^2=0 | | 4=3x-18 | | 66-(7x+6)=7(x+2)+x | | 12x-x^2=12.8 | | 22r+18=32r-24 | | a+4a-21=0 | | x^2+49x-380=0 | | -4v+6v=-16 | | 4x^4+2x^3-39x^2+43x-10=0 | | 6x-8x+10=87-21+10x | | x-(-11)=18 | | -7(2t+3)=-35 | | s*4-46=-2 | | 49x+1.5=25x+3 | | 3x-7-4x+11=6x-3 | | 12a+12a+7a+7a= | | 40c+8=48c-20 | | -30=-5+5 | | 3x-7-4x+11=6x-7 | | 2f=10 | | 10+5(a-3)=9-2a | | tg(2x)=0.6 | | 2z^2-15z+7=0 | | 7(x-6)=56 | | x^2-10x+6=1 | | 7(3s+4)=133 | | 3z+3z+4z+3+4z+3=132 | | 3f=9 |

Equations solver categories